PERENCANAAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 4.1 (STUDI KASUS PT. NETWAVE TEKNOLOGI) - Indriyani, Fintri (Jurnal Pilar Nusa Mandiri, 2013)
The existence of Information Systems aims to meet the information needs of companies that support the business processes cannot be separated from the support of a good information technology services. The factors that influence the level of maturity of IT service utilization in PT. Netwave Technology is standardized and clear documentation that must be owned by either the IT department in terms of human resources, aligning IT goals with business goals, data management, security management, and fulfillment of the needs of other divisions. The current maturity level of IT services at PT. Netwave Technology has been measured based on COBIT 4.1 framework is still at the level of two (Repeatable) in which it shows there are still some deficiencies that must be corrected immediately. At this writing aims to make strategic planning of IS / IT to align with business objectives. Where the results of this study obtained several strategies that can be used by PT. Netwave Technology to meet the information needs that support the business processes of the company.